2017
DOI: 10.7196/samj.2017.v107i10.12821
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and early removals of Implanon NXT in South Africa: Perceptions and attitudes of healthcare workers

Abstract: Background. The South African (SA) government introduced Implanon NXT, a long-acting subdermal contraceptive implant, in 2014 to expand contraceptive choice. Following an initial high uptake, its use declined considerably amid reports of early removals and frequent side-effects. We examine providers' perceptions of training and attitudes towards Implanon NXT, as well as their views on the causes of early removals and the impact on the implant service. Objective. To assess healthcare providers' perceptions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 18 publications
12
42
0
Order By: Relevance
“…The methods used to select the facilities and the results of other components of the evaluation have been detailed elsewhere. [9,10] We extracted contact details of women aged >18 years who had had an implant inserted since 2014 (n=751). In total, 262 of these women agreed to be interviewed, with the remainder either not contactable (telephone number not recorded or invalid), or not willing to participate.…”
Section: Participant Recruitmentmentioning
confidence: 99%
“…The methods used to select the facilities and the results of other components of the evaluation have been detailed elsewhere. [9,10] We extracted contact details of women aged >18 years who had had an implant inserted since 2014 (n=751). In total, 262 of these women agreed to be interviewed, with the remainder either not contactable (telephone number not recorded or invalid), or not willing to participate.…”
Section: Participant Recruitmentmentioning
confidence: 99%
“…[30] SA data also indicate that training that is too short and does not include management of side-effects and removals, may be inadequate to support implant provision. [31,32] Pre-insertion counselling and ongoing support Adopt a 'LARC first' structured approach to contraceptive counselling. The content of contraceptive counselling heavily influences method selection, especially among younger women.…”
Section: Fy 2015 Fy 2016 Fy 2017mentioning
confidence: 99%
“…[53] Although health workers in SA commonly prescribe treatment for bleeding and headaches related to the implant, medication regimens vary considerably and a standardised approach is needed. [31,32] Health workers' resistance to removals, or other failures in accessing removal services, will rapidly tarnish the implant's image and potentially undermine the entire family planning programme. Service delivery capacity for removals is a problem in many places [54] and women often resort to private sector providers.…”
Section: Fy 2015 Fy 2016 Fy 2017mentioning
confidence: 99%
“…Providers could raise this as an option, but then must inform women to consider the possibility of conflict with their partner, even violence, should the device be discovered. Clearly, providers' confidence and competence to deliver a new contraceptive are critical to its success, as discussed by Adeagbo et al [4] in a study of nurses in this edition of SAMJ. They found that providers generally felt inadequately prepared to carry out counselling, offer follow-up support and undertake removals.…”
Section: Counselling and Choicementioning
confidence: 99%
“…Use of the implant has since declined, but currently accounts for ~7% of all contraceptive use -a not insignificant achievement for a 'new' method . [1,2] In this edition of SAMJ, three articles [3][4][5] take stock of the early years of implant provision in SA. The articles, based on research in 2016, capture women's motivations for using the implant and their perspectives towards the method; and healthcare providers' competencies and experiences with service provision.…”
Section: Cmementioning
confidence: 99%